Scenario forecasting after the great recession - Sarmiento, Camilo (Albert Tavidze, 2017)
This chapter examines the implication of the Great Recession for scenario forecasting of home prices. The testing results indicate that data periods used in estimation prior to the Great Recession contributed to the generation of stress scenarios that were unable to foresee as a possibility the home price declines that were observed during the Great Recession. The empirical analysis thus shows the presence of large model risk prior to the Great Recession due to data filters. To account for this source of model risk, the paper considers an alternative approach for determining stress scenarios that are less sensitive to the data.

Este capítulo examina las implicaciones de la Gran Recesión para Predicción de escenarios de precios de viviendas. Los resultados de las pruebas indican que los datos Los períodos utilizados en la estimación antes de la Gran Recesión contribuyeron a la generación de escenarios de estrés que no se pudieron prever como posibilidad las caídas de los precios de las viviendas que se observaron durante la Gran Recesión. El análisis empírico muestra así la presencia de un gran riesgo de modelo antes a la Gran Recesión debido a los filtros de datos. Para dar cuenta de esta fuente de riesgo del modelo, el documento considera un enfoque alternativo para determinar escenarios de estrés que son menos sensibles a los datos.
Keywords: Crisis financiera global, 2008-2009; Global Financial Crisis, 2008-2009; Crisis económica; Depressions; Vivienda - Aspectos económicos; Housing - Economic aspects; Economía financiera; Financial economics